Attending 5th Varian Oncology Summit 2019: Learning Experiences as a Medical Physicist - Sudaram, Venugopal (Europasian Journal of Medical Sciences, 2019)
The main objective of the conference was to provide insights into new innovation and technology-related products by Varian to its global users, thus aiming to facilitate better and advance treatment to every cancer patients. Varian organized this summit to create a platform for its users to share their experience and knowledge not only in India but also the neighbouring country such as Nepal, Bangladesh, etc. The need for radiotherapy center in our country Nepal has been growing rapidly yet there are only a few radiotherapy centers with less or not enough needed technical resources and manpower (Radiation oncologists (ROs), Medical physicists (MPs), Radiotherapy Technologists (RTT’s)). Many radiotherapy centers still followed basic treatment modality only. However, due to the lack of high-end treatment techniques such as Intensity Modulated Radiation Therapy (IMRT), Volumetric Modulated Arc Therapy (VMAT), Stereotactic Radio Surgery (SRS) and Stereotactic Radio Therapy (SRT) in Nepal, it poses a great burden to patients as they have to travel outside the country to get better quality treatment.